Screening BRCA1 and BRCA2 unclassified variants for splicing mutations using reverse transcription PCR on patient RNA and an ex vivo assay based on a splicing reporter minigene. Issue 7 (18th April 2008) - Bonnet, C; Krieger, S; Vezain, M; Rousselin, A; Tournier, I; Martins, A; Berthet, P; Chevrier, A; Dugast, C; Layet, V; Rossi, A; Lidereau, R; et al.
Abstract : Background: Many unclassified variants (UV) of BRCA1 or BRCA2 may have an effect on pre-mRNA splicing. Patient blood samples suitable for RNA extraction are not always available for testing UVs at the RNA level. Methods: Analyses of RNA from patient peripheral blood were performed, using a one-step reverse transcriptase-PCR (RT-PCR) protocol, and were compared with an ex vivo splicing assay based on PCR-amplified patient DNA inserted into a splicing reporter minigene. Using both methods 20 variants found in 17 patients were examined. Results: Data from patient RNA and from the minigene assay were fully concordant, but the ex vivo splicing assay, which is monoallelic, clarified several ambiguities in the patient RNA data. Two intronic variants induced strong splicing defects: BRCA1 c.4987-5T→A (IVS16-5T→A) induced exon 17 skipping and BRCA2 c.316+5G→C (IVS3+5G→C) induced complete skipping of exon 3. Of the exonic variants, BRCA2 c.7805G→C (p.Arg2602Thr), at the last base of exon 16, induced both exon skipping and activation of a cryptic exonic donor site, and BRCA2 c.8023A→G (p.Ile2675Val) generated a strong donor site within exon 18. These four variants were thus classified as pathogenic, because of the total absence of a normal transcript from the corresponding allele. Variant BRCA2 c.9501+3A→T (IVS25+3A→T) induced incomplete skipping of exon 25, suggesting a mutation with incomplete penetrance, and BRCA2 c.8257_8259del (p.Leu2753del) modified the alternative splicing of exons 17 and 18. Conclusions: We show that functional analysis using a splicing reporter minigene is sensitive and specific, and should be used for initial screening of potential splicing defects, especially when patient RNA is not readily available.